Apathy and Antipathy: Media Coverage of Restrictive Immigration Legislation and the Maintenance of Symbolic Boundaries1. Issue 3 (15th April 2016) - Estrada, Emily P.; Ebert, Kim; Lore, Michelle Halla
Abstract : Although the government no longer explicitly establishes boundaries of whiteness, it continues to play a central role in shaping symbolic boundaries between immigrants and nonimmigrants through immigration lawmaking. However, the salience of these boundaries may depend on how the media disseminate them to the public. In this study, we investigate media framing of immigration lawmaking using an original data set of news coverage of six of the most widely recognized exclusionary immigration bills and laws at different levels of government. Two patterns emerged from an iterative frame analysis. First, in their coverage of frames critical of these bills and laws, outlets devoted more attention to the effects of exclusionary legislation for nonimmigrants. Second, in their coverage of frames supportive of the restrictive legislation, outlets provided more space to those who openly associated immigrants with criminality and terrorism. Regardless of outlets' seemingly neutral stance toward restrictive legislation, their disparate coverage of exclusionary lawmaking demonstrates apathy and antipathy toward immigrants, which has repercussions for the maintenance of inequality.